(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
The main ancient testimonies about the great temporal cycles of the Celtic world are the calendar of Coligny and the saeculum cited by Pliny NH 16.250. It is uncertain how the two cycles were synchronized. The different circular motifs on the lunula with geometric decoration from the Chão de Lamas treasure (Miranda do Corvo, Coimbra, Portugal) coincide with the months of the five-year period in the Coligny calendar and with the number of lustra of the Celtic saeculum. Together, they seem to represent a period of 114 years, equivalent to six Metonic cycles, from which 53 days would be deleted. These 53 days play a significant role in the Baile in Scáil. Therefore, we reflect on the value that historical homology can have as a tool for analysing protohistoric objects.